A new species of Havelockia Pearson, 1903 from the Argentine Sea (Holothuroidea: Dendrochirotida: Sclerodactylidae) - Martinez, Mariano Ignacio (2013)
Havelockia pegi sp. nov., is here described from shallow waters of the Argentine Sea. This new species is distinctive in the purple colouration of its tentacles, scarcity of body wall ossicles and the presence of rosette-shaped ossicles in both the introvert and the tentacles. It is not closely related to any of its congenors. This is the first record of a true sclerodactylid from Argentina. Thandarum hernandezi Martinez & Brogger, 2012, described in the family Sclerodactylidae, is now classified in the family Sclerothyonidae.